تعارض الرفع والوقف : دراسة نظرية تطبيقية - العازمي، محمد عزيز (جامعة الكويت - مجلس النشر العلمي, 2011)
تعد مسألة تعارض الوقف والرفع من المسائل المهمة الواردة في قضية الاختلافات في الأسانيد والمتون، بل ومن أصعبها وأدقها. ولقد قمت بدراسة هذا الوضع من خلال مبحثين: \ قمت في الأول: بدراسة مصطلحي الرفع والوقف لغة واصطلاحا؛ للوقوف على التمييز بينهما. \ ثم طرحت في المبحث الثاني أربعة مطالب ملحة إذا ما وجد تعارض بين الوقف والرفع وهى كالتالي: \ المطلب الأول: تصحيح الوجهين رفعا ووقفا وتوصلت من خلال ذلك إلى أربع حالات يرجح فيها حفظ الراوي ولا يوهم فيصح الوجهان رفعا ووقفا وهي: \ 1-\ أن يروى مرفوعا وموقوفا والموقوف مما لا مجال للرأي فيه. \ 2-\ أن يروى مرفوعا وموقوفا ويصرح الراوي بأنه وقفه. \ 3-\ أن يروى مرفوعا وموقوفا ويحمل المرفوع على الرواية والموقوف على الفتوى. \ 4-\ أن يروى مرفوعا وموقوفا ويكون الراوي معروفا بوقفه الرواية. \ المطلب الثاني: ترجيح الرفع وإعلال الوقف، ومن ذلك: حالتان، الأولى: أنه إذا جاء مرفوعا في الصحيحين أو أحدهما ترجح الثانية إذا جاء الحديث بصيغة محتملة للرفع وجاء من طريق أخرى مرفوعا رجح الرفع. \ المطلب الثالث: ترجيح الوقف وإعلال الرفع، ومن ذلك: أن ينكر الراوي رفعه فيرجح الوقف، أو أن يرجع الراوي عن الرفع فيرجح الوقف، أو أن يكون المرفوع ضعيفا والموقوف له حكم الرفع فيرجح الموقوف، أو أن يأتي الحديث مرفوعا وموقوفا ثم يأتي في رواية تبين أنه مدرج، أو أن يروى الحديث جماعة موقوفا ويرفعه واحد فيرجح الوقف. \ المطلب الرابع: إعلال الوجهين رفعا ووقفا، وذلك إذا اضطربت الروايات واختلفت، فتعل، والاختلاف المؤثر هو المشعر بقلة ضبط راويه... The issue of the opposition of Waqf and Raf’ is one of the important issues in differences of references and texts of Hadiths even the most difficult and specific. I have made my research into two topics. The first one dealt with the two words of Raf’ and Waqf from lexical as well as scientific perspectives to make it easy to differentiate between them. I exposed four issues in the second part. They are exacting demands in case of opposition between Waqf and Raf. \ They are as follows:- \ First topic : Correction of Raf and Waqf. I reached that through 4 cases in which learning of the narrator by heart. Both correct. They are as follows : \ 1\ - To be narrated as both Raf and Waqf-The mawqoof is taken for \ granted. \ 2\ - To be narrated as marfoo’ and mawqoof - The narrator admits \ that he had made it mawqoof. \ 3\ - To be narrated as marfoo’ and mawqoof - marfoo depends on \ narration and mawqoof depends on Fatwa. \ 4\ - To be narrated as marfoo’ and mawqoof. The narrator is known \ for his Waqf of the narration. \ Second topic : overweigh Raf and weaken Waqf in two cases . \ 1st : If it comes marfoo’ in both Sahihs or one of them. It will be overweighed. \ 2nd : If the Hadith comes as propable marfoo’ and comes in another way marfoo’ - Raf will be overweighed. \ Third demand : Overweigh Waqf and weaken Raf’ as for example : The narrator made it marfoo’, the Waqf will be overweighed. Or the narrator changed his opinion of Raf in this case Waqf is overweighed or marfoo’ is weak and mawqoof has the judgment of Raf in this case mawqoof is overweighed. Or the Hadith comes marfoo’ and mawqoof and in another narration it is recorded "mudraj" or the Hadith is narrated by a group as mawqoof except for one who says it is marfoo’ here Waqf is overweighed. \ 4th demand : (weakening both points) Raf and Waqf - in case narrations contradicted and differed,. They will be weak. Effective difference is that which makes you feel there is inaccuracy of narration
Keywords: الاحاديث النبوية -- الرفع و الوقف -- الوقف -- الأسناد في الحديث -- رواة الحديث -- الروايات -- علوم الحديث